2014
DOI: 10.1371/journal.pone.0110318
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Rank and Eigenface Based Sparse Representation for Face Recognition

Abstract: In this paper, based on low-rank representation and eigenface extraction, we present an improvement to the well known Sparse Representation based Classification (SRC). Firstly, the low-rank images of the face images of each individual in training subset are extracted by the Robust Principal Component Analysis (Robust PCA) to alleviate the influence of noises (e.g., illumination difference and occlusions). Secondly, Singular Value Decomposition (SVD) is applied to extract the eigenfaces from these low-rank and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The investigational results had shown that the categorization accurateness of NNC is greater than that of single feature domain. Improved SRC face recognition system using low-rank representation and eigenface extraction has been presented in [13]. Initially, robust PCA extraction is applied to the low-rank images of the face images of each individual in training subset to lessen the effect of occlusions and illumination difference.…”
Section: Introductionmentioning
confidence: 99%
“…The investigational results had shown that the categorization accurateness of NNC is greater than that of single feature domain. Improved SRC face recognition system using low-rank representation and eigenface extraction has been presented in [13]. Initially, robust PCA extraction is applied to the low-rank images of the face images of each individual in training subset to lessen the effect of occlusions and illumination difference.…”
Section: Introductionmentioning
confidence: 99%